Analysis of Market Orientation and Product Innovation on Competitive Advantage - Wati, Sukma Septya; Joansyah, Dicky; Saori, Sopyan (Dinasti Publisher, 2024)
The development of the traditional food industry has intensified competition among MSMEs. This study aims to analyze the effect of market orientation and product innovation on competitive advantage in traditional food MSMEs in Sukabumi City. The research method uses a causal descriptive quantitative approach with a sample of 128 traditional food MSMEs. Data were collected through questionnaires, interviews, literature study, and documentation. Data analysis used multiple linear regression. The results showed that market orientation had no significant effect on competitive advantage, while product innovation had a positive and significant effect on competitive advantage. Simultaneously, market orientation and product innovation have a significant effect on competitive advantage with a contribution of 15%. This finding indicates that traditional food MSMEs in Sukabumi City need to focus more on product innovation to improve their competitive advantage. This study provides insights for MSME players and related stakeholders in developing strategies to improve the competitiveness of traditional food MSMEs in an increasingly competitive era.